Strengthening Sustainable Northern Food Systems: Federal Policy Constraints and Potential Opportunities - Wilson, Amanda; Levkoe, Charles Z.; Andrée, Peter; Skinner, Kelly; Spring, Andrew; Wesche, Sonia; Galloway, Tracey (ARCTIC, 2020)
This paper explores how Canadian federal policy and frameworks can better support community-basedinitiatives to reduce food insecurity and build sustainable food systems in the North. Through an examination of the current state of food systems infrastructure, transportation, harvest, and production in the Yukon, Northwest Territories, Nunavut, Nunavik, and Nunatsiavut, we argue in favour of a multi-sector approach that supports diversified food systems, including traditional/country food production and distribution, in a way that values and prioritizes community-led initiatives and Indigenous peoples’ self-determination and self-governance. The challenge of developing sustainable, northern food systems requires made-in-the-North solutions that are attuned to cultural, geographic, environmental, and political contexts. Recent policy developments suggest some progress in this direction, however much more work is needed. Ultimately, sustainable northern food systems must be defined by and for Northerners at community, local, and regional levels, with particularattention paid to treaty rights and the right to self-determination of First Nations and other Indigenous communities. Cet article se penche sur la manière dont les politiques et les cadres de référence fédéraux du Canada peuvent mieuxsoutenir les initiatives communautaires afin d’atténuer l’insécurité alimentaire et d’édifier des systèmes alimentaires durables dans le Nord. En nous appuyant sur l’examen de l’état actuel de l’infrastructure des systèmes alimentaires, du transport, des récoltes et de la production du Yukon, des Territoires du Nord-Ouest, du Nunavut, du Nunavik et du Nunatsiavut, nous plaidons en faveur d’une approche multisectorielle favorisant des systèmes alimentaires diversifiés, y compris la production et la distribution d’aliments traditionnels ou du terroir, valorisant et priorisant les initiatives communautaires de même que l’autodétermination et l’autonomie gouvernementale des peuples autochtones. Le défi consistant à concevoir des ...